2013
DOI: 10.1007/s13157-013-0498-6
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Reserve Program Enhances Site Occupancy and Species Richness in Assemblages of Anuran Amphibians in the Mississippi Alluvial Valley, USA

Abstract: We measured amphibian habitat use to quantify the effectiveness of conservation practices implemented under the Wetland Reserve Program (WRP), an initiative of the U.S. Department of Agriculture's Natural Resources Conservation Service. From February to June 2007, we quantified calling male anurans in cultivated cropland, former cultivated cropland restored through the WRP, and mature bottomland hardwood forest. Sites were located in two watersheds within the Mississippi Alluvial Valley of Arkansas and Louisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Variation in number of species detected in this study among wetlands is consistent with results of numerous amphibian studies, especially anurans (e.g., Church 2008;Walls et al 2013). Variation in numbers and relatively small sample sizes contributed to the lack of significant differences in species richness among the wetlands I sampled.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Variation in number of species detected in this study among wetlands is consistent with results of numerous amphibian studies, especially anurans (e.g., Church 2008;Walls et al 2013). Variation in numbers and relatively small sample sizes contributed to the lack of significant differences in species richness among the wetlands I sampled.…”
Section: Discussionsupporting
confidence: 88%
“…My results showed that restored wetlands support levels of amphibian diversity similar to the reference natural wetlands included in this study. They also demonstrate the effectiveness of conservation efforts implemented under NRCS wetland programs, and support the findings of Balas et al (2012), , and Walls et al (2013), who studied amphibians in other regions. Wetlands restored through NRCS and private landowner partnerships, such as those included in this study, support amphibian populations that help mitigate natural habitat loss in these two regions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Since 1992, the United States Department of Agriculture (USDA) Natural Resources Conservation Service (NRCS, ) has invested large sums in restoring wetlands on over 900,000 ha of agricultural land as Wetland Reserve Easements under the Agricultural Conservation Easement Program, also referred to as the Wetlands Reserve Program (WRP). Although studies such as Walls, Waddle, and Faulkner () support the success of the WRP in restoring suitable wetland habitat through amphibian surveys, the ability of conservation efforts to mitigate historical wetland loss and degradation is still questioned. There is also a recurring conclusion that many restoration efforts fail to establish a proper hydrological regime (Kirk, Wise, & Delfino, ; Kusler & Kentula, ; National Research Council, ) or are poorly managed (Stroman & Kreuter, ) and, therefore, may ultimately fail in restoring the full function of the wetland.…”
Section: Introductionmentioning
confidence: 99%
“…The MAV assessment compares active croplands, afforested WRP tracts, and mature bottomland hardwood (BLH) forests to quantify multiple services including pollutant reduction, wildlife habitat, and biodiversity support (e.g. Waddle et al ; Walls et al ). Preliminary data for overstory tree composition suggested that WRP and BLH sites shared about 70% of species (both planted and colonizing), indicating a potential to resemble natural forests with time.…”
Section: Introductionmentioning
confidence: 99%